0
$\begingroup$

let $X$ and $Y$ be two exponential random variables with the same parameter $\lambda$. I try to calculate the MGF of random variable $V=X-Y$ given that $X>Y$. We know that the MGF of Exponential random variables are $M_X(t)=M_Y(t)=\frac{\lambda}{\lambda-t}$. Further, because of the memoryless property of exponential random variables, if $X$ and $Y$ are independent, then $V$ is an exponential random variable with parameter $\lambda$. However, I try to calculate the MGF of $V$ directly as follows:

$$E[e^{tV}|X>Y]=\int_0^\infty E[e^{t(X-Y)}|X>Y=y]dF_Y(y)$$ $$E[e^{t(X-Y)}|X>Y=y]=\int_y^\infty e^{t(X-y)}\lambda e^{-\lambda x} dx=\frac{\lambda e^{-\lambda y}}{\lambda-t}$$ therefore: $$M_V(t)=E[e^{tV}|X>Y]=\int_0^\infty \frac{\lambda e^{-\lambda y}}{\lambda-t}dF_Y(y)=\int_0^\infty \frac{\lambda e^{-\lambda y}}{\lambda-t}\lambda e^{-\lambda y} dy=\frac{1}{2}\frac{\lambda}{\lambda-t}$$ i dont know why the final result is different from $M_X(t)$ by factor of$\frac{1}{2}$

$\endgroup$

1 Answer 1

1
$\begingroup$

This is incorrect: $$E[e^{t(X-Y)}|X>Y=y]=\int_y^\infty e^{t(X-y)}\lambda e^{-\lambda x} dx$$

The reason is becuase $$\operatorname{E}[g(X) \mid X > y] \ne \int_{x=y}^\infty g(x) f_X(x) \, dx,$$ because $$\int_{x=y}^\infty f_X(x) \, dx \ne 1.$$ The expectation must always be calculated over a proper density that integrates to $1$.

Instead, $$\operatorname{E}[e^{t(X-y)} \mid X > y] = \int_{x=y}^\infty e^{t(x-y)} \lambda e^{-\lambda(x\color{red}{-y})} \, dx.$$ This however, still implicitly uses the memoryless property as justification. You could also write

$$\operatorname{E}[g(X) \mid X > y] = \frac{\int_{x=y}^\infty g(x) f_X(x) \, dx}{\int_{x=y}^\infty f_X(x) \, dx}.$$ Here, the conditional distribution is $X \mid X > y$ and has density $$f_{X \mid X > y}(x) = \frac{f_X(x)}{S_X(y)}$$ where $S_X = 1 - F_X$ is the survival function.

$\endgroup$
2
  • $\begingroup$ Thanks a lot for your clear answer $\endgroup$ Mar 27 at 19:07
  • $\begingroup$ Excuse me, here we cant write $E[e^{t(X-Y)}|X>Y]$ piecewise like $E[e^{tX}|X>Y]E[e^{-tY}|X>Y]$, is it right? $\endgroup$ Mar 28 at 6:06

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.